Self-repairing heat-insulating spray coating suitable for low-pressure steam pipeline and preparation method of self-repairing heat-insulating spray coating
By combining modified waste aluminum silicate refractory staple fiber and self-repair composite powder, self-repair thermal insulation spray coating is prepared, which solves the problem of degradation of thermal insulation performance and difficulty in automatic repair during long-term use of steam pipeline insulation materials, and realizes the problem of the problem of thermal insulation performance degradation and difficulty in automatic repair. The stability of thermal insulation performance and the extension of service life.
Patent Information
- Application Number
- CN202411369987.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-29
AI Technical Summary
During long-term use of existing steam pipeline insulation materials, there are problems such as deterioration of structural and material properties, falling off and breaking, and large heat loss, and lack of automatic repair mechanisms, resulting in a decrease in thermal insulation performance and shortening of service life.
Self-repair thermal spray coatings are prepared by modified waste aluminum silicate refractory staple fiber and self-repair composite powder. The fiber performance is improved through ultrasonic vibration screening and polyethylene glycol modification treatment, combined with self-crosslinked acrylate emulsion and medium Materials such as ammonium polyphosphate form porous thermal insulation materials, achieving self-repair of cracks and improving thermal insulation performance.
It realizes the stability and service life of steam pipes, and has the advantages of convenient construction, low cost and good waterproofness, which solves the degradation of thermal insulation performance and difficulty in automatic repair during service in the prior art. question.
Smart Images

Figure BDA0005067323260000111 
Figure HDA0005067323290000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal insulation materials, and in particular relates to a self-repairing thermal insulation spray coating suitable for a low-pressure steam pipeline and a preparation method thereof. Background Art
[0002] Steam is one of the most critical energy sources in national pillar industries such as steel, petrochemicals, etc. In particular, steel enterprises generally have more steam generating ends and more dispersed use ends. The steam pipeline network has complex structure, wide coverage and long mileage. It is an important energy medium transportation channel.
[0003] At present, the main problems with steam pipeline insulation include: the types of insulation materials and insulation structures are single, and soft insulation materials or hard insulation materials are used. For example, although soft insulation materials such as aluminum silicate needle-punched blankets and rock wool felts have the advantages of good vibration resistance and convenient construction, there is a common problem of loose insulation structure sinking during use. Hard insulation materials such as microporous calcium silicate series products have good strength, are not easy to be compressed, and have little effect on thermal conductivity, but there are problems such as fragility during construction and transportation, difficulty in construction on special-shaped parts, and easy cracking during use. In addition, with the extension of the service life, unfavorable factors such as the decline in the thermal insulation performance of the insulation material itself, cracking of the protective layer, and poor waterproof performance of the insulation material are all reasons for excessive pipeline heat dissipation.
[0004] In response to the above problems, patent CN109488838B discloses a steam pipe insulation material and its construction process, introduces a variety of insulation materials including aerogel technology, and adopts a multi-layer composite insulation method to improve the insulation and waterproof performance of the steam pipe insulation layer. However, the multi-layer wrapping method leads to many construction steps, difficult splicing parts, and large actual interlayer thermal resistance. Patent application CN108409200A discloses a method for preparing a high-strength and stable pipeline insulation material. The scheme uses granite as a raw material to prepare granite fiber, and after the granite fiber is organically treated, a composite aerogel material is added therein. While improving the insulation performance of the insulation material, the excellent mechanical properties of the granite fiber itself are used to improve the strength of the insulation material, but it cannot solve the problem of poor waterproofness of aerogel nanomaterials.
[0005] In response to the problems existing in steam pipe insulation, the insulation performance can be improved to a certain extent by adopting new low-thermal conductivity aerogel technology and adding multi-layer composite insulation structure. However, it cannot effectively solve the problems such as the poor waterproof performance of aerogel nanomaterials. Usually, an additional waterproof layer is required for protection. Once the waterproof layer is damaged, the aerogel nanomaterials in the insulation layer will be damaged. In addition, the existing technology has not yet proposed a solution for the automatic repair of cracks and damage in steam pipe insulation materials during their service life. Summary of the invention
[0006] The main purpose of the present invention is to provide a self-repairing thermal insulation spray coating suitable for low-pressure steam pipes. The spray coating has the advantages of excellent thermal insulation performance, self-repair of cracks, long service life, low cost, good waterproofness and convenient construction. It can effectively solve the problems of structural and material performance degradation, shedding and damage, large heat loss, etc. of existing steam pipe insulation materials during long-term use; and the preparation cost involved is low, environmentally friendly, and suitable for promotion and application.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, comprising the following raw materials in weight percentage: 23-37% of modified waste aluminum silicate refractory short fibers, 15-25% of self-repairing composite powder, 10-15% of lightweight floating beads, 5-10% of accelerator, 25-35% of binder, 1-3% of composite water reducer, and 0.05-0.15% of retarder; the modified waste aluminum silicate refractory short fibers are obtained by ultrasonically vibrating and screening waste aluminum silicate refractory fibers and performing surface modification using a polyethylene glycol solution; and the modified waste aluminum silicate refractory short fibers include two sizes of 1-1.5 mm and 3-5 mm.
[0009] Furthermore, the contents of the modified waste aluminum silicate refractory short fibers having sizes of 1 to 1.5 mm and 3 to 5 mm are 8 to 15% and 15 to 22% respectively.
[0010] Preferably, the waste aluminum silicate refractory fibers are taken from industrial waste whose working environment is an oxidizing atmosphere and whose medium- to long-term working temperature is lower than 900°C, or from industrial waste whose working environment is a reducing atmosphere and whose medium- to long-term working temperature is lower than 700°C.
[0011] Furthermore, the vibration screening step includes: shearing the waste aluminum silicate refractory fibers into short fibers of 3 to 5 mm, and then screening them using a vibration screen with an aperture of 3 mm to remove the deteriorated refractory fibers that have become brittle and powdered due to high-temperature crystallization, and taking the part on the sieve to obtain waste aluminum silicate refractory short fibers of 3 to 5 mm; then taking a part of the obtained 3 to 5 mm waste aluminum silicate refractory short fibers and further shearing them into short fibers of 1 to 1.5 mm, and screening them using a vibration screen with an aperture of 1 mm to obtain waste aluminum silicate refractory short fibers of 1 to 1.5 mm.
[0012] Furthermore, the vibrating screen is an ultrasonic vibrating screen. When the vibrating screen motor is turned on, the ultrasonic wave generated by the ultrasonic generator is coupled to break and screen out the deteriorated refractory fibers that have become brittle and powdered due to high-temperature crystallization.
[0013] Furthermore, the ultrasonic vibration screen adopts an ultrasonic power of 0.55-1.1 kW, a vibration frequency of 20-30 kHz, an amplitude of 15-20 um, and a vibration time of 3-5 min.
[0014] Furthermore, the concentration of the polyethylene glycol solution is 0.7-0.8 g / 100 mL.
[0015] Furthermore, the surface modification step includes: sending the waste aluminum silicate refractory short fibers into a closed spray operation chamber through a conveyor belt, a rotary sprayer is arranged on the top of the spray operation chamber to spray the polyethylene glycol solution, a nozzle is arranged at the bottom of the conveyor belt, and the waste aluminum silicate refractory fibers are blown into the air by blowing compressed air to fully contact with the polyethylene glycol spray. After the spraying is completed, they are sent out of the spray operation chamber through a conveyor belt and left to stand (15 to 20 minutes).
[0016] Furthermore, for a unit amount of waste aluminum silicate refractory fibers (1 kg), the spraying amount of the polyethylene glycol solution is 100 to 150 mL.
[0017] In the above scheme, the self-repairing composite powder comprises self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and water.
[0018] Furthermore, in the self-repairing composite powder, the raw materials and their mass percentages include: 25-40% self-crosslinking acrylic emulsion, 10-20% medium ammonium polyphosphate, 2-5% dipentaerythritol, 5-10% melamine, 15-30% aluminum silicate powder, and 15-25% water.
[0019] In the above scheme, the self-healing composite powder is obtained by stirring self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and water in proportion (10 to 20 minutes), drying (110 to 130° C.), breaking up and grinding.
[0020] In the above solution, the particle size of the self-repairing composite powder is less than 1200 mesh.
[0021] In the above scheme, the self-crosslinking acrylic ester emulsion is anionic, the main synthetic monomers are acrylic ester and methacrylic ester, the solid content is more than 40%, the average particle size is 0.2-0.4 μm, and the pH value is 6.0-8.0.
[0022] Furthermore, the degree of polymerization of the medium ammonium polyphosphate is 500-800.
[0023] In the above scheme, the particle size of the aluminum silicate powder is less than 1600 mesh.
[0024] Furthermore, the aluminum silicate powder is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers.
[0025] Furthermore, the high-energy ball milling treatment uses a planetary high-energy ball mill with a rotation speed of 450-550r / min, a ball milling time of 3-6h, a medium filling rate of 0.3-0.45, and a ball-to-material ratio of (3-5):1.
[0026] Furthermore, the high-energy ball milling treatment introduces a grinding aid, the amount of which is 3-6% of the mass percentage of the 1-1.5 mm waste aluminum silicate refractory short fibers; specifically, anhydrous ethanol or the like can be selected.
[0027] Preferably, the particle size of the light floating beads is 80-200 mesh, and the bulk density is ≤0.43g / cm 3 .
[0028] Preferably, the coagulant is sintered magnesia powder, with a MgO content of ≥98wt% and a particle size of less than 300 meshes.
[0029] In the above scheme, the binder includes silica sol and water-based silicone resin.
[0030] Furthermore, in the silica sol, the SiO2 content is 30-40wt%, and the pH value is 9.0-9.5; the water-based silicone resin is an ionic water-based silicone resin with a temperature resistance of ≥400°C, a solid content of ≥45%, and a pH value of 6.0-8.0.
[0031] Furthermore, the mass ratio of the silica sol to the water-based silicone resin is (4-10):1.
[0032] In the above scheme, the composite water reducer includes polycarboxylic acid high-efficiency water reducer and sodium tripolyphosphate.
[0033] Furthermore, the water reduction rate of the polycarboxylic acid high-efficiency water reducing agent is 30-40%.
[0034] Furthermore, the mass ratio of the polycarboxylate high-efficiency water reducer to sodium tripolyphosphate is 1:(6.5-25).
[0035] Preferably, the retarder is citric acid.
[0036] The present invention also provides a method for preparing a self-repairing thermal insulation spray coating suitable for a low-pressure steam pipeline, comprising the following steps:
[0037] 1) Weigh the modified waste aluminum silicate refractory short fibers, self-repairing composite powder, lightweight floating beads, accelerator, binder, composite water reducer and retarder according to the proportion; first add part of the modified waste aluminum silicate refractory short fibers and the entire amount of lightweight floating beads into a mixer, stir (3 to 5 minutes), then add the weighed self-repairing composite powder, accelerator and retarder, add the remaining amount of aluminum silicate refractory short fibers under stirring conditions, stir (5 to 10 minutes), and obtain a solid mixture;
[0038] 2) The solid mixture and the binder are mixed and stirred evenly (5 to 10 minutes) to obtain the self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines.
[0039] In the above scheme, in step 1), the modified waste aluminum silicate refractory staple fibers include modified waste aluminum silicate refractory staple fibers with lengths of 3-5 mm and 1-1.5 mm, respectively. During the feeding process, 2 / 3 of the modified waste aluminum silicate refractory staple fibers with a length of 3-5 mm and the whole amount of the modified waste aluminum silicate refractory staple fibers with a length of 1-1.5 mm are added first; and then (after adding the self-healing composite powder, accelerator and retarder) the remaining amount of modified waste aluminum silicate refractory staple fibers with a length of 3-5 mm is added.
[0040] The self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines prepared according to the above scheme needs to complete the spraying construction within 30 minutes; it is suitable for thermal insulation protection of low-pressure steam pipelines with steam temperatures of 230 to 360°C.
[0041] The principle of the present invention is:
[0042] The present invention improves the thermal insulation performance of the area close to the hot surface of the pipeline through the design of low thermal conductivity self-repairing materials, and at the same time forms porous thermal insulation materials through self-expansion to fill and make up for cracks, thereby realizing automatic repair of the thermal insulation materials, and solving the problems of structural and material performance degradation, shedding and damage, and large heat loss in the long-term use of existing steam pipeline thermal insulation materials: through the design of self-repairing materials, aluminum silicate powder is used as the thermal insulation filler, medium polyammonium phosphate + dipentaerythritol + melamine is combined as the foaming expansion agent, and self-crosslinking acrylic ester emulsion is introduced as the bonding agent, and the thermal insulation filler and the foaming expansion agent are wrapped therein through self-crosslinking polymerization reaction. At the same time, melamine also acts as a crosslinking agent to provide a large number of free radicals, which synergistically promote the interface bonding between the self-crosslinking acrylic ester emulsion and the powder particles to form a composite particle self-repairing material with a core-shell structure, thereby improving the stability and waterproofness of the material. When the low-pressure steam pipe is in normal operation (steam temperature 230-360℃), the temperature of the adjacent area in contact with the steam pipe rises (≥200℃), and the volume expansion caused by heat foaming forms a porous thermal insulation material. The porous thermal insulation material itself has a low thermal conductivity and can fill the gaps between the refractory fibers, further improving the thermal insulation performance. In addition, as the service time continues to increase, the thermal insulation material itself will inevitably shrink and crack, and the structure and performance will deteriorate. When cracks appear inside and heat is conducted outward through the gaps, the thermal insulation performance of the thermal insulation layer decreases, and the temperature around the cracks rises. When the temperature exceeds 200℃, the self-repairing material around the cracks expands due to the heat, forming a porous thermal insulation material to fill and make up for the cracks, realizing the automatic repair of the material during the service process, and achieving the purpose of improving the overall thermal insulation performance and extending the service life.
[0043] Aluminum silicate refractory fibers discarded from metallurgical furnaces are used as the main raw materials to prepare waste aluminum silicate refractory short fibers and aluminum silicate powder. The raw materials are cheap, easy to obtain, and of high purity. The good thermal insulation ability of refractory fibers is utilized to improve the thermal insulation performance and tensile strength of the spray coating, while reducing carbon dioxide emissions and environmental pollution. In order to solve the technical problems of performance degradation caused by crystallization, pulverization, hardening, and easy breakage of discarded aluminum silicate refractory fibers, the improvement measures adopted are as follows: First, the source of the raw materials is screened. By selecting aluminum silicate refractory fibers used in the thermal insulation layer of metallurgical furnaces, the long-term working temperature in an oxidizing atmosphere is lower than 900°C or the long-term working temperature in a reducing atmosphere is lower than 700°C, which is lower than the significant crystallization temperature of aluminum silicate refractory fibers (950°C in an oxidizing atmosphere and 750°C in a reducing atmosphere), which greatly reduces the crystallization temperature of discarded aluminum silicate refractory fibers. The ratio of crystals; secondly, the aluminum silicate refractory fiber is sheared and screened by ultrasonic vibration screen. When the vibration screen motor is turned on, the ultrasonic wave generated by the ultrasonic generator is coupled to the characteristics of high density and fragility of crystallization fiber relative to amorphous fiber. The deteriorated crystallization refractory fiber that has become brittle and powdered at high temperature is broken and screened out. At the same time, the deteriorated slag balls and crystallization particles attached to the surface of normal refractory fiber that are difficult to screen out with conventional mechanical vibration screens can be removed by ultrasonic vibration, further improving the thermal insulation performance and stability of the recycled waste aluminum silicate refractory fiber. Finally, in order to improve the toughness of aluminum silicate refractory fiber, improve the interface bonding of refractory fiber and its dispersion state in the spray coating, the surface of the waste refractory fiber is sprayed with a polyethylene glycol aqueous solution with a concentration of 0.7-0.8g / 100mL. The efficiency and uniformity of the modification operation are improved by spraying at the top of the spray operation chamber and blowing at the bottom.
[0044] By adding lightweight floating beads and utilizing their typical hollow spherical closed pore microstructure, the number of micron-level closed pores is increased, further reducing the thermal conductivity. At the same time, the good fluidity of spherical particles is utilized to improve the construction performance of the spray coating.
[0045] By adding sintered magnesia sand coagulant with a particle size of less than or equal to 300 mesh, the physical and chemical effects between magnesium oxide, silica sol and water-based silicone resin are utilized to promote the reaction of anions on the surface of the sol, accelerate the formation and gelation rate of the siloxane group, and accelerate the coagulation and bonding of the binder. The spray coating can be hardened quickly and the curing time can be significantly shortened (to 2 hours), thereby shortening the construction period.
[0046] By using silica sol and water-based silicone resin as composite binders, the pH value can be adjusted to effectively control the curing time of the material to meet the construction requirements. At the same time, the silica sol is hydrated and gelled and crystallized inside the material. A large number of micropores generated during molding can further improve the thermal insulation performance. In addition, the water-based silicone resin is coated on the surface of the refractory fiber and the powder, and its hydrophobicity is used to improve the waterproof performance of the spray coating insulation layer, reduce the impact of rainwater leakage on the insulation layer during the use of the steam pipeline, and improve the service life. The present invention uses a composite binder based on silica sol and water-based silicone resin, which can effectively ensure the mechanical properties and bonding properties of the coating system on the basis of controlling costs.
[0047] By adding citric acid retarder, citric acid is reacted with MgO particles in sintered magnesia to form a low-solubility magnesium citrate protective layer, which can control the hydration rate of magnesium oxide, thereby reducing the viscosity of the binder, improving the fluidity of the spray coating, promoting the coagulation and hardening of the matrix, and improving the strength.
[0048] Through the optimized combination of polycarboxylic acid high-efficiency water-reducing agent and sodium tripolyphosphate, the performance shortcomings of a single water-reducing agent are avoided, the construction fluidity of the spray coating is improved, and the amount of binder is reduced, achieving the effect of high water reduction rate and no segregation.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] 1) The self-repairing thermal insulation spray coating for low-pressure steam pipes described in the present invention has the advantages of self-repairing of cracks, stable thermal insulation performance and long service life, which effectively solves the problems that the thermal insulation performance of existing low-pressure steam pipe insulation materials drops sharply after cracking, shrinkage, loosening and settlement, and cannot be repaired online in a hot state; by exploring the degradation mechanism of the thermal insulation structure of steam pipe insulation materials under long-term service and the temperature distribution law inside the insulation layer after degradation, a self-repairing material suitable for low-pressure steam pipes (steam temperature 230-360°C) is invented, which realizes the automatic repair of the material during service, thereby achieving the purpose of improving the overall thermal insulation performance and extending the service life.
[0051] 2) Compared with the traditional steam pipe insulation process of multi-layer insulation blanket + heat radiation reflection layer + waterproof layer wrapping, the present invention adopts the method of spray construction + hot surface self-expansion fastening + material waterproof component design, which has the advantages of convenient construction, strong integrity, good waterproofness, and high comprehensive thermal insulation performance. While reducing the work intensity, it avoids the problems of air leakage caused by loose wrapping and overlapping seams in the construction of multi-layer insulation blankets.
[0052] 3) The present invention uses discarded aluminum silicate refractory fibers, lightweight floating beads, etc. as main raw materials, combined with the design of self-expanding porous thermal insulation materials when working under temperature, to fully fill the gaps between the refractory fibers, which can effectively overcome the problems of low strength, large shrinkage, and fast decay of thermal insulation performance of conventional fiber spray coatings, realize high value-added resource utilization of discarded refractory materials, and has the advantages of low preparation cost and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 This is a scanning electron microscope photograph of the self-repairing composite powder in the sample after the self-repairing thermal insulation spray coating for low-pressure steam pipes obtained in Example 1 was heat-treated at 300°C for 3h and then expanded and grew when exposed to heat. DETAILED DESCRIPTION
[0054] The following will be a clear and specific description of the technical solutions used in the present invention through examples and comparative examples. The examples and comparative examples are only examples of the present invention, do not represent all examples, and do not limit the scope of the present invention. The embodiments of the present invention, as well as various changes or modifications made by those skilled in the art according to the present invention, these equivalent forms also belong to the scope of protection of the present invention.
[0055] In the following examples, the waste aluminum silicate refractory fibers are taken from waste aluminum silicate refractory fiber blankets / modules for cold rolling and annealing furnace linings (oxidizing atmosphere, medium- and long-term operating temperature 700-900° C.).
[0056] The preparation method of the modified waste aluminum silicate refractory fiber comprises the following steps: 1) shearing the recovered waste aluminum silicate refractory fibers into short fibers of 3 to 5 mm, and then screening them with an ultrasonic vibration screen with an aperture of 3 mm (ultrasonic power 0.55 to 1.1 kW, vibration frequency 20 to 30 kHz, amplitude 15 to 20 um, vibration time 3 to 5 min), while the vibration screen motor is turned on, coupling the ultrasonic wave generated by the ultrasonic generator to break and screen out the deteriorated refractory fibers that have become brittle and powdered due to high-temperature crystallization, so as to obtain 3 to 5 mm waste aluminum silicate refractory short fibers; 2) then taking part of the waste aluminum silicate refractory short fibers and further shearing them into short fibers of about 1 to 1.5 mm, and screening them with an ultrasonic vibration screen with an aperture of 1 mm, and removing the deteriorated slag balls and crystallization particles attached to the surface of the normal refractory fibers that are difficult to be screened out with a conventional mechanical vibration screen through ultrasonic vibration, so as to obtain 1 to 1.5 mm waste aluminum silicate refractory short fibers. Abandoned aluminum silicate refractory short fibers; 3) finally, the obtained 3-5 mm abandoned aluminum silicate refractory short fibers and 1-1.5 mm abandoned aluminum silicate refractory short fibers are respectively sent into a closed spray operation chamber through a conveyor belt, and a rotary sprayer is arranged at the top of the spray operation chamber to spray polyethylene glycol PEG-4000 aqueous solution (wherein the concentration adopted in Examples 1, 2, and 5 is 0.7 g / 100 mL, and the spraying amount is 150 mL / Kg; the concentration adopted in Examples 3 and 4 is 0.8 g / 100 mL; the spraying amount is 100 mL / Kg), and a nozzle is arranged at the lower part of the conveyor belt, and the abandoned aluminum silicate refractory short fibers are blown into the air by blowing compressed air to fully contact with the polyethylene glycol spray. After the spraying is completed, they are sent out of the spray operation chamber through a conveyor belt and allowed to stand (15-20 min), and 3-5 mm modified abandoned aluminum silicate refractory short fibers and 1-1.5 mm modified abandoned aluminum silicate refractory short fibers are respectively obtained.
[0057] In the following examples, the silica sol is provided by Guangdong Huierte Nano Technology Co., Ltd., and its SiO2 content is 40% and the pH value is 9.0-9.5; the water-based silicone resin used is an ionic water-based silicone resin, provided by Shenyang Caiyi Special Coatings Co., Ltd., with a temperature resistance of ≥400°C, a solid content of ≥45%, and a pH value of 6.0-8.0.
[0058] The polycarboxylic acid high-efficiency water-reducing agent used is WSM-M polycarboxylic acid high-efficiency water-reducing agent provided by Hubei Sman New Materials Co., Ltd., and its water reduction rate is ≥35%.
[0059] The self-crosslinking acrylic emulsion used is provided by Kunshan Development Zone Lianle Chemical Trading Co., Ltd., model la-1025, which is anionic, the main synthetic monomers are acrylate and methacrylate, the solid content is ≥40%, the average particle diameter is 0.2-0.4um, and the pH value is 6.0-8.0.
[0060] Example 1
[0061] A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, the raw material components and weight percentages thereof are:
[0062] Modified waste aluminum silicate refractory short fibers 28% (3-5mm modified waste aluminum silicate refractory short fibers 10%, 1-1.5mm modified waste aluminum silicate refractory short fibers 18%); self-repairing composite powder 22%; 200-mesh lightweight floating beads 11.3%; 300-mesh sintered magnesia powder (MgO content ≥ 98%) 6%; binder 30% (24% silica sol, 400°C temperature-resistant ionic water-based silicone resin 6%); composite water reducer 2.6% (0.1% WSM-M polycarboxylic acid high-efficiency water reducer, 2.5% sodium tripolyphosphate); 0.1% citric acid retarder;
[0063] The self-repairing composite powder used has a particle size of 1200 mesh, and the raw materials and their mass percentages are: 30% self-crosslinking acrylic emulsion, 15% medium ammonium polyphosphate (polymerization degree 800), 4% dipentaerythritol, 6% melamine, 30% aluminum silicate powder (particle size 1600 mesh), and 15% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;
[0064] The aluminum silicate powder (1600 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers.
[0065] The method for preparing the self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines comprises the following steps:
[0066] 1) The weighed modified waste aluminum silicate refractory fibers, self-repairing composite powder, lightweight floating beads, coagulant, composite water reducer and retarder are first added into a mixer with two-thirds of the amount of 3-5 mm modified waste aluminum silicate refractory short fibers and the entire amount of 1-1.5 mm modified waste aluminum silicate refractory short fibers and lightweight floating beads, stirred for 5 minutes, and then the self-repairing composite powder, coagulant and retarder are added at one time, and the remaining amount of 3-5 mm modified waste aluminum silicate refractory short fibers is gradually added while stirring, and stirring is continued for 10 minutes to obtain a solid mixture, which is packaged in a waterproof sealed package with a shelf life of 6 months;
[0067] 2) Packaging of binder mixture: Weigh silica sol and water-soluble silicone resin according to weight percentage, stir for more than 5 minutes, mix evenly, and prepare binder, which is packaged in plastic barrels with a shelf life of 12 months;
[0068] 3) On-site construction of spray material: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 6 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 120 minutes at an ambient temperature of 30°C.
[0069] Example 2
[0070] A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:
[0071] 1) The raw materials and their mass percentages are: 35% of modified waste aluminum silicate refractory short fibers (15% of 3-5mm modified waste aluminum silicate refractory short fibers, 20% of 1-1.5mm modified waste aluminum silicate refractory short fibers); 15% of self-repairing composite powder; 15% of lightweight floating beads with a particle size of 200 mesh; 7% of sintered magnesia powder with a particle size of 300 mesh (MgO content ≥ 98%); 25% of binder (20% of silica sol, 5% of ionic water-based silicone resin with a temperature resistance of 400°C); 2.95% of composite water reducer (0.3% of WSM-M polycarboxylic acid high-efficiency water reducer, 2.65% of sodium tripolyphosphate); 0.05% of citric acid retarder;
[0072] The self-repairing composite powder used has a particle size of 1200 mesh, and the raw materials and their mass percentages are: 40% self-crosslinking acrylic emulsion, 10% medium ammonium polyphosphate (polymerization degree 800), 2% dipentaerythritol, 5% melamine, 25% aluminum silicate powder (particle size 1600 mesh), and 18% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain the self-repairing composite powder;
[0073] The aluminum silicate powder (1600 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers.
[0074] 2) On-site construction of spray material: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 180 minutes at an ambient temperature of 10°C.
[0075] Example 3
[0076] A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:
[0077] 1) The raw materials and their mass percentages are: 30% of modified waste aluminum silicate refractory short fibers (8% of 3-5mm modified waste aluminum silicate refractory short fibers, 22% of 1-1.5mm modified waste aluminum silicate refractory short fibers); 20% of self-repairing composite powder; 10% of lightweight floating beads with a particle size of 80 meshes; 10% of sintered magnesia powder with a particle size of 300 meshes (MgO content ≥ 98%); 28% of binder (25% of silica sol, 3% of ionic water-based silicone resin with a temperature resistance of 400°C); 1.95% of composite water reducer (0.15% of WSM-M polycarboxylic acid high-efficiency water reducer, 1.8% of sodium tripolyphosphate); 0.05% of citric acid retarder;
[0078] The self-repairing composite powder used has a particle size of 1200 mesh, and the raw materials and their mass percentages are: 25% self-crosslinking acrylic emulsion, 20% medium ammonium polyphosphate (polymerization degree 500), 5% dipentaerythritol, 10% melamine, 15% aluminum silicate powder (particle size 1600 mesh), and 25% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding, and obtaining a self-repairing composite powder;
[0079] The aluminum silicate powder (1600 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers.
[0080] 2) On-site construction of spray material: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 150 minutes at an ambient temperature of 10°C.
[0081] Example 4
[0082] A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:
[0083] 1) The raw materials and their mass percentages are: 30% of modified waste aluminum silicate refractory short fibers (15% of 3-5mm modified waste aluminum silicate refractory short fibers, 15% of 1-1.5mm modified waste aluminum silicate refractory short fibers); 19% of self-repairing composite powder; 15% of lightweight floating beads with a particle size of 120 mesh; 5% of sintered magnesia powder with a particle size of 300 mesh (MgO content ≥ 98%); 28% of binder (23% of silica sol, 5% of ionic water-based silicone resin with a temperature resistance of 400°C); 2.9% of composite water reducer (0.3% of WSM-M polycarboxylic acid high-efficiency water reducer, 2.6% of sodium tripolyphosphate); 0.1% of citric acid retarder;
[0084] The self-repairing composite powder used has a particle size of 1300 mesh, and the raw materials and their mass percentages are: 25% self-crosslinking acrylic emulsion, 20% medium ammonium polyphosphate (polymerization degree 500), 5% dipentaerythritol, 10% melamine, 15% aluminum silicate powder (particle size 1700 mesh), and 25% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up and grinding to obtain a self-repairing composite powder;
[0085] The aluminum silicate powder (particle size of 1700 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers;
[0086] 2) On-site construction of spray material: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 120 minutes at an ambient temperature of 30°C.
[0087] Example 5
[0088] A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, the preparation method of which is substantially the same as that of Example 1, except that:
[0089] 1) The raw materials and their mass percentages are: 25% of modified waste aluminum silicate refractory fibers (9% of 3-5 mm modified waste aluminum silicate refractory short fibers, 16% of 1-1.5 mm modified waste aluminum silicate refractory short fibers); 25% of self-repairing composite powder; 10.7% of lightweight floating beads with a particle size of 120 mesh; 5% of sintered magnesia powder with a particle size of 400 mesh (MgO content ≥ 98%); 33% of binder (30% of silica sol, 3% of ionic water-based silicone resin resistant to 400°C); 1.15% of composite water reducer (0.15% of WSM-M polycarboxylic acid high-efficiency water reducer, 1% of sodium tripolyphosphate); 0.15% of citric acid retarder;
[0090] The self-repairing composite powder used has a particle size of 1300 mesh, and the raw materials and their mass percentages are: 25% self-crosslinking acrylic emulsion, 20% medium ammonium polyphosphate (polymerization degree 600), 5% dipentaerythritol, 10% melamine, 15% aluminum silicate powder (particle size 1700 mesh), and 25% deionized water; the specific preparation steps include: weighing the self-crosslinking acrylic emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and deionized water in proportion, mixing and stirring in a blender for 15 minutes, drying at 110°C, breaking up, and grinding to obtain a self-repairing composite powder;
[0091] The aluminum silicate powder (particle size of 1700 mesh) is obtained by high-energy ball milling of 1-1.5 mm waste aluminum silicate refractory short fibers;
[0092] 2) On-site construction of spray material: Weigh the solid raw materials and binder in proportion, add them into the stirrer and stir for 10 minutes. After mixing evenly, use special spraying equipment to spray the surface of the steam pipe. The construction should be completed within 30 minutes and solidify within 120 minutes at an ambient temperature of 30°C.
[0093] Comparative Example 1
[0094] The low-pressure steam pipeline of a steel plant (steam pressure 1.8MPa, temperature 350℃, pipe diameter 325mm) uses rock wool shell as insulation layer, with a thickness of 40mm and a bulk density of 150kg / m 3 , maximum operating temperature 450℃, thermal conductivity 0.081W / m·K (hot surface temperature 300℃).
[0095] Comparative Example 2
[0096] The low-pressure steam pipeline of a steel plant (steam pressure 1.8MPa, temperature 350℃, pipe diameter 325mm) is wrapped with aluminum silicate wool needle-punched blanket with a thickness of 40mm and a bulk density of 128kg / m 3 , maximum operating temperature 1000℃, thermal conductivity 0.087W / m·K (hot surface temperature 300℃).
[0097] According to the self-repairing thermal insulation spray coatings for low-pressure steam pipelines of Examples 1 to 5, standard samples were prepared, cured in a natural environment, demolded after 12 hours, and heat treated at 300°C for 3h to test the bulk density, compressive strength and thermal conductivity. The bulk density of each sample was between 0.35 and 0.46 g / cm 3 The compressive strength is between 0.21 and 0.35 MPa, and the thermal conductivity (hot surface temperature 300°C) is between 0.08 and 0.10 W / m·K. The scanning electron microscope photo of the self-repairing composite powder in the sample after heat treatment at 300°C × 3h for the self-repairing thermal insulation spray coating for low-pressure steam pipeline in Example 1 after self-expansion growth when heated is shown in the following figure. Figure 1 As shown. According to Examples 1 to 5, the self-repairing thermal insulation spray coating for low-pressure steam pipelines was prepared, and the low-pressure steam pipelines of a steel plant (steam pressure 1.8MPa, temperature 350°C, pipe diameter 325mm, insulation layer thickness 40mm) were tested and applied. Compared with Comparative Examples 1 to 2, the material performance indicators and application effects are shown in Table 1. Compared with the prior art, it has the advantages of excellent thermal insulation performance, crack self-repair, long service life, low cost, good waterproofness and convenient construction.
[0098] Table 1 Performance indicators and application effects of the embodiments of the present invention and the comparative examples
[0099]
[0100] Comparative Example 3
[0101] A self-repairing thermal insulation spray coating, whose preparation method is roughly the same as that of Example 1, except that: in the preparation method of the modified waste aluminum silicate refractory fiber, the vibration screening adopts a conventional mechanical vibration screen, wherein the vibration frequency adopted is 20-30kHz, the amplitude is 15-20um, and the vibration time is 3-5min.
[0102] The thermal conductivity of the prepared standard sample is 0.112 (W / m·K) when the hot surface temperature is 300°C, which is greater than the thermal conductivity of Example 1. In addition, after one year of use in the on-site industrial test, the average outer surface temperature of the pipeline is 25°C, which is also higher than that of Example 1.
[0103] Comparative Example 4
[0104] A self-repairing thermal insulation spray coating, the preparation method of which is roughly the same as that of Example 1, except that the self-crosslinking acrylic emulsion is replaced by the water-based acrylic emulsion produced by Qingdao Enze Chemical Co., Ltd. Since it cannot self-crosslink, an additional crosslinking agent needs to be added during the preparation of the self-repairing composite powder, and the mixture is heated to 150°C and kept warm for 60 minutes. The thermal conductivity of the prepared standard sample is 0.127 (W / m·K) at a hot surface temperature of 300°C, which is greater than the thermal conductivity of Example 1.
[0105] Comparative Example 5
[0106] A self-repairing thermal insulation spray coating, the preparation method of which is roughly the same as that of Example 1, except that the mass percentages of the raw materials in the self-repairing composite powder used are as follows: 30% self-cross-linking acrylic emulsion, 15% medium polyammonium phosphate (degree of polymerization 800), 4% dipentaerythritol, 36% aluminum silicate powder (particle size 1600 mesh), and 15% deionized water.
[0107] Using the above-mentioned self-healing composite powder formulation system, the self-cross-linking reaction of the self-cross-linking acrylic emulsion is not sufficient within the same reaction time, and the composition of the prepared self-healing composite powder is uneven; the thermal conductivity of the prepared standard sample is 0.121 (W / m·K) when the hot surface temperature is 300°C, which is greater than the thermal conductivity of Example 1.
[0108] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines, characterized in that: The invention comprises the following raw materials in weight percentage: 23-37% of modified waste aluminum silicate refractory short fibers, 15-25% of self-repairing composite powder, 10-15% of lightweight floating beads, 5-10% of accelerator, 25-35% of binder, 1-3% of composite water reducer and 0.05-0.15% of retarder; the modified waste aluminum silicate refractory short fibers are obtained by ultrasonically vibrating and screening waste aluminum silicate refractory fibers and performing surface modification with polyethylene glycol solution; and the fibers include two sizes of 1-1.5 mm and 3-5 mm.
2. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The contents of the modified waste aluminum silicate refractory short fibers with sizes of 1 to 1.5 mm and 3 to 5 mm are 8 to 15% and 15 to 22% respectively.
3. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The vibration screening step includes: shearing the waste aluminum silicate refractory fibers into short fibers of 3 to 5 mm, and then screening them with a vibration screen with a pore size of 3 mm to obtain waste aluminum silicate refractory short fibers of 3 to 5 mm; then taking part of the obtained 3 to 5 mm waste aluminum silicate refractory short fibers and further shearing them into short fibers of 1 to 1.5 mm, and screening them with a vibration screen with a pore size of 1 mm to obtain waste aluminum silicate refractory short fibers of 1 to 1.5 mm.
4. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The surface modification step comprises: spraying a polyethylene glycol solution on the waste aluminum silicate refractory short fibers.
5. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The self-repairing composite powder comprises self-crosslinking acrylic ester emulsion, medium ammonium polyphosphate, dipentaerythritol, melamine, aluminum silicate powder and water.
6. The self-repairing thermal insulation spray coating according to claim 5, characterized in that: The raw materials and their mass percentages in the self-repairing composite powder include: 25-40% self-crosslinking acrylic emulsion, 10-20% medium ammonium polyphosphate, 2-5% dipentaerythritol, 5-10% melamine, 15-30% aluminum silicate powder, and 15-25% water.
7. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The binder includes silica sol and water-based silicone resin.
8. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The composite water reducing agent comprises a polycarboxylate high-efficiency water reducing agent and sodium tripolyphosphate.
9. The self-repairing thermal insulation spray coating according to claim 1, characterized in that: The coagulant is sintered magnesia powder; the retarder is citric acid.
10. The method for preparing the self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh the modified waste aluminum silicate refractory short fibers, self-repairing composite powder, lightweight floating beads, accelerator, binder, composite water reducer and retarder according to the proportion; first add part of the modified waste aluminum silicate refractory short fibers and the entire amount of lightweight floating beads into a mixer, stir, then add the weighed self-repairing composite powder, accelerator and retarder, add the remaining amount of aluminum silicate refractory short fibers under stirring, stir to obtain a solid mixture; 2) The solid mixture and the binder are mixed and stirred evenly to obtain the self-repairing thermal insulation spray coating suitable for low-pressure steam pipelines.
Citation Information
Patent Citations
Preparation method of high strength stable type pipe insulation material
CN108409200A
A thermal insulation material for steam pipes and its construction process
CN109488838B
Thermal insulation coating material for propane dehydrogenation device and preparation method of thermal insulation coating material
CN112960986A
Quick-drying hollow sphere heat-insulating refractory castable
CN113636831A
Self-repairing solvent-free epoxy fireproof coating and preparation method thereof
CN113930135A
